Generational differences and motivation in the food industry - Kőmüves, Zsolt; Hopp, Alexandra; Szabó-Szentgróti, Gábor (Studia Mundi – Economica, 2022)
In the face of changing economic and environmental factors, labour turnover remains one of the key issues for companies. As one of the unanticipated effects of the pandemic, managers have been confronted with the fact that workers' reactions have changed, changing jobs more frequently and more quickly.  In our study, we analysed the motivational differences between generations. Literature evidence shows that significant differences in generational values have emerged and should be prioritised in motivation and incentives. Our research was carried out among employees of large food companies. Data were collected using a snowball method, in which a database of 126 respondents was developed. ANOVA analysis and LSD post hoc test were used for data analysis. The results show that there is evidence of motivational differences between generations, which managers need to build on in their motivational strategies and practices. Generation Z and Y employees have more difficulty identifying with organisational goals and are more likely to plan to change jobs. Organizations need to shift the paradigm in their internal communication practices to ensure that corporate "messages" reach all employees.